2006
DOI: 10.1093/bja/ael270
|View full text |Cite
|
Sign up to set email alerts
|

The effects of propofol on neutrophil function, lipid peroxidation and inflammatory response during elective coronary artery bypass grafting in patients with impaired ventricular function

Abstract: Propofol attenuates free-radical-mediated lipid peroxidation and systemic inflammation in patients with impaired myocardial function undergoing CABG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(56 citation statements)
references
References 24 publications
(16 reference statements)
3
48
0
1
Order By: Relevance
“…However, propofol possesses diverse actions including anti-inflammatory properties, activation of atypical PKC isoforms, and inhibition of mitochondrial permeability transition that could confer protection against ischemia/ reperfusion [8,[17][18][19][20]. The results of the present study are consistent with our previous work, suggesting that propofol's effects cannot be explained strictly on the basis of an antioxidant mechanism.…”
Section: Discussionsupporting
confidence: 91%
“…However, propofol possesses diverse actions including anti-inflammatory properties, activation of atypical PKC isoforms, and inhibition of mitochondrial permeability transition that could confer protection against ischemia/ reperfusion [8,[17][18][19][20]. The results of the present study are consistent with our previous work, suggesting that propofol's effects cannot be explained strictly on the basis of an antioxidant mechanism.…”
Section: Discussionsupporting
confidence: 91%
“…Due to their similar chemical structures, propofol has analogous biochemical functions to those of Vitamin E, including anti-oxidative, mitochondrial protective and free-radical scavenging activity (31)(32)(33). Furthermore, propofol inhibits the phosphorylation of JNK (30,34). These results therefore indicated that the mechanism underlying the inhibitory effect of propofol on AQP-4 and MMP-9 may be via inactivation of the JNK pathway.…”
Section: Discussionmentioning
confidence: 78%
“…In contrast, the intravenous anaesthetic, propofol, may have largely protective effects 6, 11, 12, 13, mainly shown in animal and cellular models, although it has also been suggested to have some negative actions 14.…”
Section: Introductionmentioning
confidence: 99%